Technology-Enabled Visualization of Team Typologies at a Multi-Institutional IPE Event - Claudia Jayne Brahler; Betsy Donahoe-Fillmore (Education Sciences, 2023)
Background: Preventable medical errors caused by ineffective teamwork are substantial contributors in the majority of patient harm events. Nonetheless, the interprofessional education (IPE) research to date has not reported on within-group interactions and discourse to determine if students in IPE teams are practicing effective teamwork at IPE events. Purpose: The overall objective of this mixed methods study was to develop IPE team typologies based on a multi-institutional IPE event in order to characterize and provide actionable knowledge for improving IPE teamwork. Methods: A total of 127 students and 18 faculty, representing eight pre-professional programs and three universities, participated in this study. The IPE teams were videotaped during their case-solving work. These recorded sessions were analyzed using a mixed methods design that included event-based scoring for cognitive level and team behaviors and development of IPE team typologies using a constant comparative analysis (open, axial, and selective coding) of 14 IPE teams during the process of developing care plans for novel patient cases. Team typologies were cross-validated with the current literature. Discussion: Four IPE team typologies emerged: Facilitated, Cohesion, Consensual Validation, and Silo Mentality (listed in rank order from most to least effective). Only the Facilitated team type demonstrated effective teamworking behaviors. Decreasing team effectiveness was met with a dose-dependent, concomitant decrease in average cognitive level and beneficial team behaviors. Conclusions: The results of this study provide the knowledge required to implement recommendations for targeted interventions to improve IPE teamwork. Effective teamwork is crucial to optimal patient care; therefore, future research should critically analyze and seek to improve IPE teamwork in order to prepare a practice-ready next generation of healthcare professionals.